An investigation on empathy of nurses in tertiary mental health institutions in Guangdong Province (广东省三级精神卫生机构护士共情能力调查分析) - ZENG Junfang (曾君芳); HAO Li (郝丽); GAN Ruiyan (甘瑞妍); ZHANG Huixian (张慧娴); TAN Huanjun (谭焕君); XIE Huajie (谢华杰); JIANG Xianquan (江先铨); CAI Hongtao (蔡红涛) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the status quo of empathy of nurses in mental health institutions, and explore the factors affecting their empathy. Methods A cross-section survey was conducted in nurses from 6 tertiary mental health institutions in Guangdong Province using the general information scale and Jefferson Scale of Empathy Health Professionals (JSE-HP). Results The average score of nurses' empathy was (82. 11±5. 46), and the total scoring rate was 58. 65%. Dimensions with scoring rate ranking from high to low were compassionate care, perspective taking and standing in the patient's shoes, respectively. Nurse level and employment type were found to be the factors influencing empathy of nurses (P<0. 05). Conclusion Empathy of nurses from tertiary mental health institutions is in a mediate level. Nursing managers should pay more attention to the mental health and needs of those N3or N4 level and temporary nurses, helping to enhance their empathy. (目的 调查广东省精神卫生机构护士共情能力现状, 探讨其影响因素, 为护理管理者针对性提升护士共情能力的水平提供参考依据。方法 采用便利抽样法, 选取广东省6所三级精神卫生机构护士作为研究对象, 使用一般调查问卷及杰弗逊共情量表(JSE-HP)进行调查。结果 精神卫生机构护士共情能力均分(82. 11±5. 46)分, 总得分率为58. 65%; 3个维度由高到低依次为情感护理、观点采择、换位思考。不同能级及聘用形式的精神卫生机构护士, 其共情能力总分差异有统计学意义(P<0. 05)。结论 精神卫生机构护士的共情能力处于中等水平, 精神科护理管理者应多关注较高能级护士及非在编护士的心理健康及需求, 提升共情能力。)